Pengolahan Buah Kelapa (Cocos nucifera L) Menjadi VCO (Virgin Coconut Oil) dengan Cara Ekstraksi - Sri Rahayu Ningsih; Jon Efendi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Coconut is a plantation plant that grows and is widely spread in various regions of Indonesia. The processing of coconut fruit (Cocos nucifera L) into VCO (Virgin Coconut Oil) through the extraction process is a method used to obtain high-quality oil. health benefits, as well as antibacterial and antioxidant properties. This study aims to examine the extraction process in processing coconut into VCO. The process begins with the selection of fresh coconuts, then the coconuts are grated and squeezed to produce coconut milk. Extraction is carried out without heating. The extraction results will produce high-quality VCO, which is characterized by clarity, a typical coconut aroma, and optimal fatty acid content. This study shows that the extraction method is effective in producing VCO with good characteristics, and can be an alternative to efficient coconut processing and economic value. Processing coconuts into VCO by extraction makes a positive contribution to the utilization of coconut natural resources and can increase the added value of processed coconut products.